Cancer-associated fibroblasts endow stem-like qualities to liver cancer cells by modulating autophagy - Zhao, Zhenxiong (Cancer Manag Res, 2019)
PURPOSE: Both cancer-associated fibroblasts (CAFs) and liver cancer stem cells (LCSCs) play an important part in the tumorigenesis, development and metastasis of hepatocellular carcinoma (HCC). Moreover, the stem-like properties in HCC cells could be promoted by CAFs. However, the mechanism remains largely unknown. PATIENTS AND METHODS: We used conditioned medium (CM) of CAFs to culture Huh7 cells. Stemness of the cells was then examined mainly by sphere formation assay while stemness-associated genes including Nanog, Sox2 and Oct4 were measured by Western blotting. Immunofluorescence staining, Transmission Electron Microscope as well as Western blotting were performed to detect the level of autophagy in Huh7 cells. RESULTS: Increased level of stemness and autophagy was observed in HCC cells cultured in CAFs-CM compared to the control group. Activation of CAFs-induced autophagic flux could be inhibited by Chloroquine (CQ), which can accumulate LC3-II protein and increase punctate distribution of LC3 localization. Treatment of HCC cells with CQ effectively reversed the CAF-induced stemness, invasion, and metastasis ability in these cells. In vivo, Huh7 cells inoculated together with CAFs developed significantly larger tumors than Huh7 cells injected alone. Moreover, blockage of autophagy in Huh7 cells by CQ greatly reduced the growth of xenografted tumors of Huh7 cells combined with CAFs. CONCLUSION: These results reveal that CAFs are capable of promoting stemness and metastasis of HCC cells and blocking autophagy could markedly attenuate the stemness enhanced by CAFs, suggesting that targeting autophagy in HCC could be an effective strategy in HCC treatment.